Semiotical Interpretation of Romance in Joko Pinurbo's Poetry: A Peircean Analysis - Audri Israh Muslimah; Samsiarni; Emil Septia (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2024)
This study aims to describe the semiotic meaning (index) in depicting romance in the poetry of Joko Pinurbo, using Charles Sanders Peirce's semiotic theory. The research employs a content analysis method, with data drawn from a selection of Joko Pinurbo's poems, including